ANALYSIS OF THE MANCHEGO CHEESE VALUE CHAIN IN CUENCA, SPAIN - Trejo Téllez Brenda Inoscencia; de los Ríos Carmenado Ignacio; Figueroa Sandoval Benjamín; Gallego Moreno Francisco José; Morales Flores, Francisco Javier (Revista Mexicana de Ciencias Agrícolas, 2018)
The value chain concept has been developed as a response to the need for rural enterprises to comply the demand requirements of high quality specialty products. This paper provides an analysis of the value chain of Manchego cheese in Cuenca, Spain; identifying actors and relations between them, where there is a significant production of Manchego cheese with designation of origin. The research was conducted during 2008 in the Province of Cuenca, Spain. Methodology used includes the following phases: 1) sector identification; 2) agents identification; 3) analysis of value chain; and 4) analysis of agents. The results obtained show that the main factors that are influencing the development of the value chain are: horizontal and vertical integration, trust between agents, access to and use of funding, compliance with government regulations, compliance with designation of origin rules. Therefore, it has been concluded that the chain is working properly and successful elements can be taken for adapting to other areas.